Lei geral de terceirização e reestruturação sindical: uma reflexão necessária - Morais, Juliana Ferreira de (2018)
The present study aims to study the legal innovations introduced in the legal system by Laws 13,429/2017 and 13,467/2017 on triangular labor relations, especially under the approach of outsourcing the end-activity and its precarious effects; and the investigation about the influence of the Brazilian trade union structure on these effects. Initially, a historical reconstruction is made with the scope of chronologically situating the emergence of the outsourcing institute and demonstrating its relations with the toyotista production model. Then the concept of the phenomenon is examined, in order to delimit its scope. It continues analyzing the legal and jurisprudential evolution, culminating with the enactment of Laws 13,429/2017 and 13,467/2017, the first laws to be dealt with regarding the general outsourcing of services in Brazil. It then reflects on the constitutionality and legality of the legal permission to outsource the service provider's final activity, as well as on the social and economic risks of the dissemination of outsourcing as a general contracting model, based on data provided by surveys in the area, on topics such as wages, work hours, length of employment, working conditions and union organization of outsourced workers. Finally, it presents a proposal for union restructuring, especially under the collective freedom of trade union approach, incompatible with the rigid criterion of aggregation by category imposed in Brazil, as a way to assure greater autonomy to outsourced workers, so that they themselves can seek, in the union of forces deriving from collective law, the solution to the problems arising from the adoption of the multiplied model of contracting, reconciling the values of human dignity with free initiative, foundations of the Federative Republic of Brazil – article 1, III and IV, of Constitution of 1988